A validation study on the performance of a horizontal axis tidal turbine (HATT) - Abuan, Binoe E. (Philippine Engineering Journal [eJournal])
A Computational Fluid Dynamics (CFD) model of the Sheffield HATT, a tidal turbine designed to perform better in varying flow velocity, was created in order to predict its performance in unsteady flow using ANSYS FLUENT. Several mesh independence tests were performed to determine a suitable mesh for the problem under study. The final CFD model was used to do simulation of a full tip-speed ratio (TSR) sweep to determine the performance curve of the turbine. It was shown that at Reynolds number, Re=125,000 (which is the same Re at the wind tunnel experiment), the shape and the trend of the performance curve has the same shape when compared to that of the initial Re at 1,350,000. Lower values of CP were obtained which agreed with a separate Blade-Element Momentum study where CP values go down as Re decreases. Brake torque experiments (using spring balance) in the wind tunnel were conducted at Re=135,000 to obtain a power curve that is plotted against the CFD simulation results. It was shown that there is good correspondence between the experimental results and the CFD results which in turn gives more confidence for the numerical data obtained from CFD simulations.